PERFORMANCE OF SOME SURFACE DRESSING TRIALS IN THE BANDUNG AREA - Justanto
A surface dressing consists of a thin film of binder, generally bitumen or tar, which is sprayed onto the road surface and then covered with a layer of single-size stone chippings. It is a maintenance procedure designed to improve skid resistance and seal cracks thereby preventing ingress of water to underlying layers. General experience indicates that the success of a surface dressing is very dependent on the adhesion of the binder, the aggregate and the road surface. The investigation described in this thesis was a study of the performance of a number of surface dressing trials in relation to adhesion and skid resistance. Factors affecting the performance of a surface dressing were investigated, especially behaviour under traffic and climatic conditions. For a variety of reasons, the experiments were largely unsatisfactory and no conclusions can be drawn with regard to the influence of such factors as size of chippings or type of binder on the efficiency of the surface treatments investigated. However, the following observations can be made: the role of the viscosity of the binder is a very important factor during the hardening process of the bitumen until satisfactory performance of the surface dressing is achieved; the skid resistance values of a surface dressing using chippings with nominal size of 12mm was quite high and will be adequate to ensure the texture depth for category A and B sites described in Road Note 27 where traffic speed is in excess of 95 km/hr. It is recommended that systematic investigation should be made of a number of surface dressings of suitable length and located in areas carrying representative traffic flows, the surface dressings to be constructed under close supervision. Investigation should include a study of the permeability of a surface dressings